Jump in! - Strickland, Shadra (Bloomsbury Children's Books, 2023)
"This bright, joyful picture book celebrates a community at play! It's a sunny spring day, and the tic tac tic tac sound of jump ropes hitting the ground floats through the wind. "Jump in!" Everyone lines up for a turn. The Delancy twins, double dutch divas. Leroy Jones with the hip-hop tricks. Even Ms. Mabel, showing the youngstas how it's done. And after a day of fun, when the street lights start to flicker, it's time to . . . jump out! With a bold graphic style, read-aloud enhancing gatefolds, and an exuberance that leaps off the page, acclaimed artist Shadra Strickland's author/illustrator debut will make readers of all ages get up on their feet!" --